The little lost Robin - Baguley, Elizabeth; Macnaughton, Tina (London : Little Tiger Press, 2008)
When a howling winter storm uproots the tree that Robin lives in, best friend Hare comes to the rescue.
3.7
K-3.
K-3
Keywords: Friendship -- Juvenile fiction; Hares -- Juvenile fiction; Robins -- Juvenile fiction; Storms -- Juvenile fiction; Friendship -- Fiction; Hares -- Fiction; Robins -- Fiction; Storms -- Fiction; Friendship -- Fiction; Rabbits -- Fiction; Robins -- Fiction; Storms -- Fiction